2016
DOI: 10.1590/s1679-45082016ao3481
|View full text |Cite
|
Sign up to set email alerts
|

Pharmaceutical orientation at hospital discharge of transplant patients: strategy for patient safety

Abstract: Objective:To describe and analyze the pharmaceutical orientation given at hospital discharge of transplant patients.Methods:This was a cross-sectional, descriptive and retrospective study that used records of orientation given by the clinical pharmacist in the inpatients unit of the Kidney and Liver Transplant Department, at Hospital Universitário Walter Cantídio, in the city of Fortaleza (CE), Brazil, from January to July, 2014. The following variables recorded at the Clinical Pharmacy Database were analyzed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
18

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(44 citation statements)
references
References 12 publications
0
22
0
18
Order By: Relevance
“…The recommendations identified in this study show that the development of a safety culture during the process of organ donation and transplantation is directly related to transplantation. Most of the studies are related to safety in the transplantation process, involving the use of medication, the participation (12) Brazil. Level IV evidence The clinical pharmacist should be part of the multiprofessional team for education of the transplant patient at the time of hospital discharge, to prevent negative results associated with pharmacotherapy, and to guarantee medication reconciliation and patient safety.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The recommendations identified in this study show that the development of a safety culture during the process of organ donation and transplantation is directly related to transplantation. Most of the studies are related to safety in the transplantation process, involving the use of medication, the participation (12) Brazil. Level IV evidence The clinical pharmacist should be part of the multiprofessional team for education of the transplant patient at the time of hospital discharge, to prevent negative results associated with pharmacotherapy, and to guarantee medication reconciliation and patient safety.…”
Section: Discussionmentioning
confidence: 99%
“…(16,24) The findings enabled the understanding that when greater patient involvement is obtained in the manipulation of medications, a greater level of treatment adherence is achieved, leading to an improvement in the patient's clinical condition, reducing infection rates, re-admission, and graft rejection. (12,(21)(22)(23) Category 2 -Culture of patient safety in the transplant units The category presents questions related to the safety culture of patients undergoing renal, (18,19) hepatic, (11) abdominal, (24) pancreatic, (20) and bone marrow transplantation, (14) in the pre-and intra-operative periods.…”
Section: Presentation Of the Categoriesmentioning
confidence: 99%
“…Five studies were found related to discharge planning (17)(18)(19)(24)(25) . Planning was centered on the health conditions of patients (19) , cognitive capacity (17,19) , social support, and the needs of patients (19) .…”
Section: Discharge Planning (Dp)mentioning
confidence: 99%
“…Professionals can and should use tools that allow a more effective orientation of care such as the creation of a map with all the medications, their respective schedules and doses described. 8 The patient who is able to understand the transplant can also change their life experience. He needs to learn how to deal with new medications, take them for the rest of his life, and adhere to lifestyle changes including hygiene practices, infection prevention, monitoring of new organ function, changes in body image, adaptation fluctuations in mood and energy level, issues of professional status, among others.…”
Section: Thementioning
confidence: 99%
“…The team should encourage transplant recipients to carry out the exams on time, as recommended by prevention programs in the country of origin. 8 The main health care for the late postoperative liver transplant patients, described from the experience of the multiprofessional team in a referral hospital, were: prevention of infections; guidance on drug therapy; guidance on returning to outpatient appointments and conducting examinations; and surgical wound care.…”
Section: Thementioning
confidence: 99%